¿Como se negocia un TLC en Colombia? / How does Colombian negotiate its free trade agreements? - Cecilia López Montaño (Colombia Internacional, 2007)
Colombia is currently involved in the second phase of globalization, characterized by trade agreements. Contrary to common belief, bilateral trade negotiations are more political than technical. Thus, the author argues that the defense of the interests of the weak demands a more political focus, under the assumption that politicians do not defend the interests of the powerful but those of the poor. However, the analysis that the article offers of the negotiation of the free trade agreement with the United States shows that the way in which President Alvaro Uribe led this process caused the country to cede too much on strategic issues affecting the interests of Colombian society.